DIGITALISASI INFORMASI TERHADAP PENYIARAN RADIO ARDAN BANDUNG - Nabila, Vira Putri; Virsa, Fathur Rorsyid; Puteri, Sanny Syaffanash Vianty (Jurnal Network Media, 2024)
Broadcasting media, namely radio and television, is a form of mass media that is efficient in reaching a very large audience. Therefore broadcast media plays a very important role in communication science in general and mass communication science in particular. The publishing industry in Indonesia shows its rapid development. One of the radio stations is Ardan Radio. This research uses a qualitative approach using the case study method. This research was carried out through an interview process, in this research an interview process was carried out with Muhamad Faisal as producer of Ardan Radio & Broadcaster in 2021 in the Ardan School school bus program. Ardan Radio Bandung has a broadcast format that prioritizes pop music, both local and international. Apart from that, they also present news, updates, and interesting segments such as talk shows, games, and interactions with listeners via telephone or social media. This radio has succeeded in building a strong image among young people and the people of Bandung. Ardan Radio has the tagline "Radio Anak Muda Bandung" which reflects its identity as a radio that presents programs that are liked by the younger generation. With the presence of Ardan Radio, listeners can enjoy their favorite music, get the latest information, and be involved in various activities and events hosted by this radio station. Ardan Radio continues to innovate and adapt to technological developments and listener preferences. They are also active in various social activities and support community events in Bandung.